2000
DOI: 10.1128/jcm.38.8.2929-2932.2000
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR for Diagnosis and Follow-Up of Toxoplasma Reactivation after Allogeneic Stem Cell Transplantation Using Fluorescence Resonance Energy Transfer Hybridization Probes

Abstract: Toxoplasma reactivation is a life-threatening complication of allogeneic stem cell transplantation. A poor prognosis is probably linked to a difficult diagnosis, based on the detection of evidence of parasites in tissue. We developed a real-time PCR test using fluorescence resonance energy transfer hybridization probes to detect and quantify Toxoplasma gondii DNA in serum. This PCR test gave reproducible quantitative results over a dynamic range of from 0.75 × 106 to 0.75 parasites per PCR mixture. Serial samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(61 citation statements)
references
References 12 publications
2
56
1
2
Order By: Relevance
“…Another study used the assay in serum for diagnosis and follow-up of four stem cell transplant patients (82). They compared their results with a conventional PCR but also were able to quantitate parasitemia using real-time PCR by correlating extracted DNA assay crossing points with corresponding tachyzoite counts of cultured Toxoplasma gondii.…”
Section: Toxoplasma Sppmentioning
confidence: 99%
“…Another study used the assay in serum for diagnosis and follow-up of four stem cell transplant patients (82). They compared their results with a conventional PCR but also were able to quantitate parasitemia using real-time PCR by correlating extracted DNA assay crossing points with corresponding tachyzoite counts of cultured Toxoplasma gondii.…”
Section: Toxoplasma Sppmentioning
confidence: 99%
“…In the present study, the sensitivity and specificity of LAMP and nested-PCR assays targeting the 529 bp RE and B1 gene were evaluated for the detection of T. gondii DNA. Due to the different studies reported a good sensitivity and specificity for the molecular markers targeting the repeated region in the T. gondii genome for detecting the parasite [6,38,39,44,45], these genomic targets were selected.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the study of new and emerging viruses has been ideally complemented by the use of homogeneous real-time PCR assays as tools to demonstrate and strengthen epidemiological links between unique viral sequences and the [177,234,240,253,254,266,267,280,284,292,294] Solid tissues [172,198,238,[256][257][258]271,288,295] Cerebrospinal fluid [136,190,192,194,248] Peripheral blood mononuclear cells [183] Bone marrow [120] Whole blood [179,291] Plasma [118] Serum [171,172,180,279,287] Swabs [192,259,296] Bronchoalveolar lavage [243,246] Amniotic fluid [286] Saliva and sputum [158,233] Faeces [264,285] Urine [12,…”
Section: Virusesmentioning
confidence: 99%